2022
DOI: 10.1111/ppc.13135
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse and aggressiveness in individuals diagnosed with schizophrenia in Lebanon

Abstract: Objectives: To identify individual and clinical risk factors of aggressiveness, including exposure to different forms of childhood trauma, in a sample of Lebanese patients with schizophrenia.Methods: A total of 131 patients diagnosed with schizophrenia participated in this cross-sectional study.Results: Higher physical (Beta = 0.24, p < 0.001) and sexual (Beta = 0.29, p = 0.003) abuse, alcohol drinking (Beta = 1.46, p = 0.008), having a history of head trauma (Beta = 1.10, p = 0.041), and male gender (Beta = −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…All these dimensions are accounted for, regardless of whether there was injury or damage caused [ 33 ]. The CASRS has previously been translated by our team using the forward and backward method [ 34 ], and has exhibited excellent psychometric properties in both Arabic-speaking clinical [ 35 ] and non-clinical populations [ 34 , 36 ]. However, in the specific context of abuse and trauma, all these scales may be challenging to administer due to their length.…”
Section: Introductionmentioning
confidence: 99%
“…All these dimensions are accounted for, regardless of whether there was injury or damage caused [ 33 ]. The CASRS has previously been translated by our team using the forward and backward method [ 34 ], and has exhibited excellent psychometric properties in both Arabic-speaking clinical [ 35 ] and non-clinical populations [ 34 , 36 ]. However, in the specific context of abuse and trauma, all these scales may be challenging to administer due to their length.…”
Section: Introductionmentioning
confidence: 99%
“…Another cross-sectional study examined a sample of Lebanese patients with schizophrenia to identify clinical risk factors for aggressiveness including child abuse. They found that higher physical and sexual abuse, alcohol drinking, having a history of head trauma, and male gender were significantly associated with higher mean aggression scores [ 57 ]. Thus, studying the factors that may affect positive symptoms of schizophrenia among the Lebanese population is crucial to provide better ways of treatment.…”
Section: Introductionmentioning
confidence: 99%